Research of the Characteristic of Hydro- viscous Clutch with Different Friction Materials - Ma Ligang; Xiang Changle; Du Minggang; Guo Liuyang (Jixie chuandong)
The friction plate gap as a key parameter which affects the towing torque is got by analyzing friction state of the hydro- viscous clutch and building mathematical model of the towing torque which combines with the specific parameter of the hydro- viscous clutch. The accuracy of the towing torque calculation model is verified by analyzing friction characteristic of hydro- viscous clutch and experimental study. The test of impact output torque is carried out which including towing torque,temperature and difference speed between two friction materials. It can be found through the test the towing torque of copper- based friction plate is about 2 times of the carbon- based friction plate with the same structure and the temperature of copper- based friction plate is higher than the carbon- based friction plate under the same experimental conditions and the change of friction coefficient with the difference speed is large. The relationship between the friction coefficient and the difference speed is fitted.